INTEGRATED CURRICULUM: SUCCESS AND CHALLENGES A review of the experience of the International Islamic School Malaysia (IISM) - Souad, Merah; Ramdane, Tahraoui (2014)
In general, Muslims: • Live in constant dualism (thoughts and convictions) • Carry nostalgic feelings towards their religious heritage. • Interact with traditional social and religious institutions (immediate families, local communities, schools…etc). However, these empathy feelings are unconsciously mixed up with secular intellectual concepts through a powerful western influence in politics, economy, culture , media and education. Such incoherent situation caused a lot of harm to the socio-cultural fabric of contemporary Muslim communities.